Impact of the duration of antibiotics on clinical events in patients with Pseudomonas aeruginosa ventilator-associated pneumonia: study protocol for a randomized controlled study. Issue 1 (December 2017) - Bouglé, Adrien; Foucrier, Arnaud; Dupont, Hervé; Montravers, Philippe; Ouattara, Alexandre; Kalfon, Pierre; Squara, Pierre; Simon, Tabassome; Amour, Julien
Abstract Background Ventilator-associated pneumonia (VAP) accounts for 25% of infections in intensive care units. Compared to a long duration (LD) of antibiotic therapy, a short duration (SD) has a comparable clinical efficacy with less antibiotic use and less multidrug-resistant (MDR) pathogen emergence, with the exception of documented VAP of non-fermenting Gram-negative bacilli (NF-GNB), includingPseudomonas aeruginosa (PA). These results have led the American Thoracic Society to recommend SD therapy for VAP, except for PA-VAP. Thus the beneficial effect of SD therapy in PA-VAP is still a matter of debate. We aimed to assess the non-inferiority of a short duration of antibiotics (8 days) versus prolonged antibiotic therapy (15 days) in PA-VAP. Methods/design The impact of the duration of antibiotics on clinical events in patients withPseudomonas aeruginosa ventilator-associated pneumonia (iDIAPASON) trial is a randomized, open-labeled non-inferiority controlled trial, conducted in 34 French intensive care units (ICUs), comparing two groups of patients with PA-VAP according to the duration (8 days or 15 days) of effective antibiotic therapy against PA. The primary outcome is a composite endpoint combining day 90 mortality and PA-VAP recurrence rate during hospitalization in the ICU. Furthermore, durations of mechanical ventilation and hospitalization, as well as number and types of extrapulmonary infections or acquisition of MDR pathogens during the hospitalization in the ICU will be recorded. Recurrence with predefined criteria (clinical suspicion of VAP associated with a positive quantitative culture of a respiratory sample) will be evaluated by two independent experts. Discussion Demonstrating that an SD (8 days) versus LD (15 days) therapy strategy in PA-VAP treatment is safe and not associated with an increased mortality or recurrence rate could lead to a change in practices and guidelines in the management of antibiotic therapy of this frequent ICU complication. This strategy could lead to decreased antibiotic exposure during hospitalization in the ICU and in turn reduce the acquisition and the spread of MDR pathogens. Trial registration ClinicalTrials.gov:NCT02634411 . Registered on 19 November 2015.